Interventions for the management of concomitant COPD and hypertension: A systematic review - Sadan Taher; Aletta E. Schutte; John R. Hurst; Chris P. Gale; Sameera Ansari (Journal of Multimorbidity and Comorbidity)
Background: Chronic obstructive pulmonary disease (COPD) and hypertension are prevalent public health burdens, with hypertension often co-existing in up to 65% of COPD patients and complicating patient management. While numerous clinical guidelines address these conditions individually, there is a scarcity of evidence-based interventions for managing both simultaneously. Purpose: This systematic review aimed to identify interventional studies targeting people with concomitant COPD and hypertension Research Design: The review followed PRISMA guidelines and was registered on PROSPERO (CRD42024533767). A comprehensive search was conducted across multiple databases, including PubMed, EMBASE, Scopus, CINAHL, the Cochrane Library and Cochrane Controlled Register of Trials. Results: The search yielded 3,348 records, of which three studies met the inclusion criteria. These studies examined interventions including oral nitrate supplementation, medication adherence management and a collaborative care model. One study reported a significant reduction in systolic blood pressure (SBP) and improvement in COPD-related outcomes, while the other two reported mixed effects. The collaborative care model notably reduced hospitalizations and healthcare costs. Conclusions: The findings highlight the limited and inconsistent evidence available for managing concomitant COPD and hypertension, reinforcing the need for further research on this topic. Despite frequent clinical encounters with patients having both conditions, practitioners lack a unified treatment strategy. Future studies should focus on developing comprehensive management approaches that address the complex interplay between COPD and hypertension, aiming to improve patients’ health outcomes and deliver efficient healthcare.